(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY/PRINCIPLES: In most centers, Upper Gastrointestinal series (UGI) following Roux-en-Y Gastric Bypass (RYGB) is performed to rule out GJ anastomotic leak. According to the introduction of robotic technology associated with a hypothetical decrease of anastomotic complications, we aim to assess the validity and cost effectiveness of early routine UGI following robot-assisted RYGB. METHODS: Between July 2006 and December 2010, 167 robot-assisted RYGB were performed at a single institution. All data were collected prospectively in a computerised database and reviewed retrospectively. Patients underwent a gastrografin UGI at postoperative day 2 to exclude anastomotic leak or stenosis. RESULTS: None of the 167 patients who underwent an early UGI experienced leak radiologically and clinically. The only radiological abnormalities were two GJ edema (1.2%) and one jejunojenunostomy stenosis (0.6%), all treated conservatively with success. The total cost for the 167 UGI was CHF 93,520 (= USD 96,886). CONCLUSIONS: In most centres, the risk of anastomotic leak has been the rationale for obtaining an UGI following RYGB. However, provided low leak rates as for our experience with robotic RYGB, the authors show this exam to be expensive and of limited value. A decisional algorithm for on demand UGI has been developed according to patient’s characteristics and is now under validation.